UPAYA PENCEGAHAN ISU KONTAMINASI MERKURI PADA IKAN DI KAWASAN PERAIRAN PULAU AMBON, PROVINSI MALUKU - Barbara Grace Hutubessy; Jacobus Bunga Paillin; Haruna Haruna; Ruslan HS. Tawari; Stany Rachel Siahainenia; M Kaledupa (Jurnal Abdi Insani, 2023)
The highest protein resource is come from fish and fish meat contains Omega-3 Fatty Acid. Unfortunately, a publication of mercury contamination on fish has created public unsettling. Unlicensed gold mining in Buru Island and cinnabar rocks in Seram Island provides plenty of job opportunities, however the tailing causes mercury contamination into the ocean. It is therefore, teach people on how to consume fish without any further mercury contamination should be done. The aims of this public service is to provoke young age people or students to eat fish. It is also to teach students avoiding of being dangerous mercury contaminated. To achieve these aims, we discussed with Prof.Dr. Y. Malle, M.Si regarding mining contamination and continued with library searched. Then we taught this information to primary student of Citra Kasih Primary school in Ambon. Focus group discussion involving a professor who is expert on mercury contamination, and he concluded that the mining has contaminated surroundings sea water. Fish also can be contaminated through food chain. The important information should be taught to the people especially the young age or students. During the innovation and outing day of Citra Kasih Primary School, this important information was taught to the students. They were so enthusiasm to learn how to eat healthy fish without being contaminated. The Omega-3 fatty acid is important for their brain and their balance, so fish meals should put in their diet menu. It is concluded that fish provide protein and contain Omega-3. Eat healthy fish is by avoiding fish head and fish body cavity to avoid contamination.